2007
DOI: 10.1016/j.pain.2006.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity related to temporal summation of C-fiber evoked pain

Abstract: Temporal summation of "second pain" (TSSP) is considered to be the result of C-fiber-evoked responses of dorsal horn neurons, termed 'windup'. This phenomenon is dependent on stimulus frequency (≥ 0.33 Hz) and relevant for central sensitization and chronic pain. Previous brain imaging studies have only been used to characterize neural correlates of second pain but not its temporal summation. We utilized functional magnetic resonance imaging (fMRI) in healthy volunteers to measure brain responses associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
162
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(179 citation statements)
references
References 44 publications
(63 reference statements)
14
162
0
3
Order By: Relevance
“…Other studies have shown activation in the cerebellum to temporal summation of C-fiber evoked pain, and suggest cerebellar activation may correlate with premotor activity (61,62). In our studies, we observed more widespread activations within the vermis and hemispheres for the patient group and in the nuclei.…”
Section: Pain and The Cerebellumsupporting
confidence: 73%
“…Other studies have shown activation in the cerebellum to temporal summation of C-fiber evoked pain, and suggest cerebellar activation may correlate with premotor activity (61,62). In our studies, we observed more widespread activations within the vermis and hemispheres for the patient group and in the nuclei.…”
Section: Pain and The Cerebellumsupporting
confidence: 73%
“…Pain-A standardized numerical pain scale (NPS) was utilized for rating the magnitude of painful sensations produced by thermal stimulation as described previously [34]. The scale ranged from 0 to 100, in increments of 5, with verbal descriptors at intervals of 10.…”
Section: Ratings Of Experimentalmentioning
confidence: 99%
“…These include areas of the brain involved in pain aŠect (ACC, insula, prefrontal cortex, and SMA) and pain modulation (ACC). 35 A previous study has reported that input from the C-ˆbers arrives at the SII and insula 500 ms after stimulation, 28 but processing is believed to be long because pain perception is a higher brain function that involves complicated and associated brain activity. Therefore, we considered that delayed and long-sustained increases in signal aŠect brain activity with real acupuncture stimulation.…”
Section: Discussionmentioning
confidence: 99%